Feeding ecology of the basking shark (Cetorhinus maximus) relative to distribution and abundance of prey - Cheryl L. Baduini (Moss Landing Marine Laboratories, 1995)
Thesis (M.S.) -- San Jose State University, 1995.by Cheryl L. Baduini."A thesis presented to the faculty of Moss Landing Marine Laboratories." "A thesis presented to the faculty of Moss Landing Marine Laboratories."